Anti-VEGF Agents for Ocular Angiogenesis and Vascular Permeability - Kenichi Kimoto; Toshiaki Kubota (Journal of Ophthalmology)
We review articles describing intravitreal injection of anti-VEGF drug trials, while discussing the mechanisms of the action of anti-VEGF antibodies, and also evaluating their outcomes. Intraocular injections of anti-VEGF drug are considered to be an effective treatment for macular edema after retinal vein occlusion, however, recurrent/persistent edema is common. The recent reports may lead to a shift in treatment paradigm for DME, from laser photocoagulation, to newer approaches using anti-VEGF drugs. There have been several well-publicized prospective, randomized studies that demonstrated the efficacy of intravitreal injection of anti-VEGF drugs for patients with AMD. Adjuvant bevacizumab for neovascular glaucoma may prevent further PAS formation, and it is likely to open up a therapeutic window for a panretinal photocoagulation and trabeculectomy. Intravitreal injection of bevacizumab (IVB) results in a substantial decrease in bleeding from the retinal vessels or new vessels during a standard vitrectomy. IVB has also been reported to be effective for inducing the regression of new vessels in proliferative diabetic retinopathy. The use of bevacizumab in stage 4 or 5 retinopahty of permaturity (ROP) is to reduce the plus sign to help reduce hemorrhage during the subsequent vitrectomy. Some authors reported cases of resolution of stage 4 A ROP after bevacizumab injection.